Small sewage wastewater treatment plants for domestic wastewater - Kyriienko, Petro G.; Betin, Oleksandr V.; Kuznetsova, Natalia V. (ІТГІП, 2018)
Small sewage wastewater treatment plants are used for treatment of domestic wastewater from individual residential houses, small schools, roadside cafes, restaurants, small railway stations, camping sites, etc., where there is no centralized sewage network. In cases when there is a limited space for the installation of small-scale treatment facilities, authors suggest using of septic tanks and drainage wells. Sewage effluents are collected with gravity force, without using electricity. Usage of proposed constructions does not cause pollution of soils and underground water horizons. Sanitary environment is stable and predictable.
Keywords: small sewage wastewater treatment plants; sewerage; household waste water; biological treatment of sewage effluents; cleaning technology; construction of treatment facilities; septic tank; drainage field; filter well; 628.56; 628.3